Role of salivary biomarkers in early detection of oral squamous cell carcinoma - Nidhi Awasthi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Oral cancer is prevalent worldwide and is a common cause of morbidity and mortality. Despite advances in treatment, the survival of patients with oral cancer has not significantly improved over the past several decades owing to late detection and treatment failures. The present study was undertaken with an objective to explore the role of salivary CYFRA 21-1, CA 19-9, lactate dehydrogenase (LDH), total proteins, and amylase as biochemical markers of oral squamous cell carcinoma (OSCC) and premalignant lesions (PML). Materials and Methods: This was a cross-sectional study for diagnostic test evaluation conducted in KGMC Lucknow, between 2010 and 2011. The study population comprised newly diagnosed cases of OSCC (Group I) and PML of oral cavity (Group II) who had not yet received any definitive therapy along with age- and gender-matched healthy controls (Group III). Unstimulated whole saliva was collected from the cases and controls. CYFRA 21-1 and CA19-9 were estimated by ELISA while LDH, total proteins, and amylase were evaluated as per standard kit method. Results: Both OSCC and PML group showed increased salivary CYFRA 21-1, LDH, and total protein concentrations as compared to controls, but the increase in PML was significantly lower as compared to OSCC. A considerable decrease in concentration of amylase was seen in OSCC and PML as compared to control group. Conclusion: The outcome of this study suggests that concurrent analysis of salivary CYFRA 21-1, LDH, total protein, and amylase can be utilized for early detection of oral cancer.